P‐elements strengthen reproductive isolation within the Drosophila simulans species complex. (1st September 2021) - Serrato‐Capuchina, Antonio; D'Agostino, Emmanuel R. R.; Peede, David; Roy, Baylee; Isbell, Kristin; Wang, Jeremy; Matute, Daniel R.
Abstract: Determining mechanisms that underlie reproductive isolation (RI) is key to understanding how species boundaries are maintained in nature. Transposable elements (TEs) are ubiquitous across eukaryotic genomes. However, the role of TEs in modulating the strength of RI between species is poorly understood. Several species of Drosophila have been found to harbor P ‐elements (PEs), yet only D. simulans is known to be currently polymorphic for their presence in wild populations. PEs can cause RI between PE‐containing (P) and PE‐lacking (M) lineages of the same species. However, it is unclear whether they also contribute to the magnitude of RI between species. Here, we use the simulans species complex to assess whether differences in PE status between D. simulans and its sister species, which do not harbor PEs, contribute to multiple barriers to gene flow between species. We show that crosses involving a P D. simulans father and an M mother from a sister species exhibit lower F1 female fecundity than crosses involving an M D. simulans father and an M sister‐species mother. We also find that another TE, I ‐element, might play a minor role in determining the frequency of dysgenesis between species. Our results suggest that the presence of PEs in a species can strengthen isolation from its sister species, providing evidence that TEs can play a role in RI.